WHY DO SPATIAL DATA AND INFORMATION HAVE A SIGNIFICANT ROLE IN SPATIAL PLANNING PROCESS? THE INVESTIGATION OF SPATIAL DATA AND INFORMATION USAGE IN INDONESIAN SPATIAL PLANNING POLICIES - Adipandang Yudono (Department of Urban and Regional Planning, Diponegoro University, 2018)
In spatial planning processes, the different aspects of human interactions involving political circumstances, social, economics, historical and cultural objectives can be understood through maps or spatial visualisations, because those media can illustrate abstract phenomena into visual images. Spatial data has a role to play in spatial governance by providing thematic spatial information and analysis at all authority scales. Furthermore, spatial data and information are prerequisites for any participation in planning deliberation helping to create consensus. Spatial data and information currently have a role in communicating with all stakeholders (i.e. local authorities, private sectors and communities) whose interests are in development proposals in particular areas in order to decide implementation, priorities in local geographical areas. This paper investigates the role of spatial data and information in Indonesian spatial planning process using archival research method. The empirical studies take a qualitative approach in analysing the results of data collection from fieldwork observation through collecting legal documents and internal institutional reports. Synchronization and consistency between development plan and spatial plan must be ensured in every interrelated spatial policy, so that the various implementation efforts do not lead to conflict. Furthermore, spatial data and information has a crucial role in translating the development strategies into the implementation of the development programme for the implementation of the government's agenda.